Nurse-Patient Communication: An Examination of Student-Nurses of Post Basic Nursing Anesthesia (PBNA) and Peri-Operative Nursing (PON) of Jos University Teaching Hospital (JUTH), Plateau State, Nigeria: Komunikasi Perawat-Pasien: Tinjauan terhadap Mahasiswa Post Basic Nursing Anesthesia (PBNA) dan Peri-Operative Nursing (PON) di Jos University Teaching Hospital (JUTH), Plateau State, Nigeria - Bwai, Patricia Nathan; Dajang, Innocent Nasuk (Journal of Literature and Education, 2024)
Effective nurse-patient communication is essential for providing high-quality healthcare and ensuring patient safety and satisfaction. Proficiency in English is crucial for nurses to effectively interact with patients, families, and other healthcare professionals. However, many nurses face challenges in using correct grammar and language, which can impact communication and care delivery. This paper explores the relevance of English proficiency in nurse-patient communication, examines the grammar challenges nurses face, and suggests potential strategies to overcome these challenges. A total of 35 student-nurses were randomly selected from the Post Basic Nursing Anesthesia (PBNA) and Peri-Operative Nursing (PON) program at JUTH. The study adopted a mixed-methods research design, combining both qualitative and quantitative data collection and analysis methods. Among other challenges, the study discovered that nurses face problems in the areas of tenses, choice of words, sentence construction, and patients’ poor grasp of English. The study suggests that language training and support, and continuous professional development, etc. can help improve the communication among nurses and with patients. The study thus concludes that proficiency in English and proper grammar usage are essential for effective nurse-patient communication, and overcoming language and grammar challenges can improve patient safety, satisfaction, and healthcare outcomes.